Iron Overload Coordinately Promotes Ferritin Expression and Fat Accumulation in Caenorhabditis elegans. Issue 1 (1st May 2016) - Wang, Haizhen; Jiang, Xue; Wu, Jieyu; Zhang, Linqiang; Huang, Jingfei; Zhang, Yuru; Zou, Xiaoju; Liang, Bin
Abstract: The trace element iron is crucial for living organisms, since it plays essential roles in numerous cellular functions. Systemic iron overload and the elevated level of ferritin, a ubiquitous intracellular protein that stores and releases iron to maintain the iron homeostasis in cells, has long been epidemiologically associated with obesity and obesity-related diseases. However, the underlying mechanisms of this association remain unclear. Here, using Caenorhabditis elegans, we show that iron overload induces the expression of sgk-1, encoding the serum and glucocorticoid-inducible kinase, to promote the level of ferritin and fat accumulation. Mutation of cyp-23A1, encoding a homolog of human cytochrome P450 CYP7B1 that is related to neonatal hemochromatosis, further enhances the elevated expression of ftn-1, sgk-1, and fat accumulation. sgk-1 positively regulates the expression of acs-20 and vit-2, genes encoding homologs of the mammalian FATP1/4 fatty acid transport proteins and yolk lipoproteins, respectively, to facilitate lipid uptake and translocation for storage under iron overload. This study reveals a completely novel pathway in which sgk-1 plays a central role to synergistically regulate iron and lipid homeostasis, offering not only experimental evidence supporting a previously unverified link between iron and obesity, but also novel insights into the pathogenesis of iron and obesity-related human metabolic diseases.